Dominant Factors Influencing Overall Temporal Sedimentation Rates at Loagan Bunut Lake, Miri, Sarawak, Malaysia - R.B., Dagang; S., Lau; Alexander Kiew, Sayok (Trans Tech Publications, 2012)
This paper is to predict dominant factors influencing temporal sedimentation rates at Loagan Bunut Lake using best-fit model of sedimentation rate and distance from Bunut River. The lake is a flood plain lake located in Sarawak, Malaysia. Twenty two cylindrical traps were installed at the lake from November 2005 until April 2008. Each sample was collected after about four to five months of deployment. Dry sedimentation rates from the traps and the linear distances from Trap 1 located at the confluence of Bunut River were measured. The factors that influence the temporal sedimentation at the lake were both internal and external physical changes of the lake. The factors were net ws (net Stoke’s settling velocity) and water volume in the lake for suspended sediment distribution.